Hubungan antara Perceived Organizational Support dengan Workplace Well-Being pada Karyawan PT Fritto Chicken Indonesia di Kota Medan - Mery Christin Panjaitan; Sri Hartini; Rianda Elvinawanty (Universitas Muhammadiyah Metro, 2026)
This study aims to examine the relationship between workplace well-being and Perceived Organizational Support (POS). The proposed hypothesis states that both variables are positively correlated. The results of the hypothesis testing indicate that workplace well-being increases when POS is high and decreases when POS is low. This study involved 127 employees of PT Fritto Chicken Indonesia in Medan City and employed a quantitative approach with a purposive sampling method. Data were analyzed using the Pearson product-moment correlation test and other statistical methods using SPSS for Windows version 25.0. The results showed a statistically significant positive relationship between POS and workplace well-being (r = 0.256, p = 0.004). However, the magnitude of the correlation is relatively low, indicating that although POS is a meaningful predictor, its practical contribution to workplace well-being is limited. The coefficient of determination (RÂ² = 0.066) further suggests that POS accounts for only 6.6% of the variance in workplace well-being, with the remaining 93.4% influenced by other factors not examined in this study. These findings imply that organizations should not rely solely on POS to enhance employee well-being but also consider other contributing factors, such as job characteristics, leadership style, and work environment. This study contributes to the literature by providing empirical evidence on the role of POS in workplace well-being within the Indonesian context, highlighting the need for a more comprehensive approach in improving employee well-being.